Media Relations dI Instansi Pemerintah (Studi Deskriptif Kualitatif Aktivitas Media Relations Humas Pemkab Karanganyar tahun 2015) - Arisandi, Fiki; , Drs. Joko Sutarso, SE, M.Si; , Agus Triyono, M.Si (2016)
PR Karanganyar government is a government agency that handles the field of communication to the public. PR Karanganyar government implement the strategy for the dissemination of information to realize a harmonious relationship with the media. Media relations or media relations have since media very spacious and almost all aspects of society could tell just by the media. Through the medium of dissemination of information is increasing with high credibility, because the media is considered an objective in the publicity. In this study will discuss how media relations public relations activities Karanganyar regency. The objective of this study was to determine the activity conducted media relations PR Karanganyar regency. This study uses descriptive qualitative data collection techniques interviews and observation. In this study concluded that the Public Relations Karanganyar government has been running a public relations strategy well as managing relationships, develop strategies and develop the network. media relations activities that do public relations such as press conferences, press releases, press interviews, press tours, press gathering, and the media visit. all activities carried out to maintain good relations with the media as well as from the two sides together to benefit of the media can obtain information to be used while the news of the PR publicity.